Food insecurity, nutritional status and socioeconomic factors in the transgender population: a cross-sectional study in the Metropolitan Region of Baixada Santista, Brazil, 2023 - Ísis Gois; Magnus Régios Dias da Silva; Barbara Iansã de Lima Barroso; Carla Gianna Luppi; Denise Leite Vieira; Katia Cristina Bassichetto (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To describe the distribution of nutritional status and food insecurity among the adult transgender population in the Baixada Santista region of the state of São Paulo and to identify associated factors. Methods This was a cross-sectional study using data from the research project entitled Mapping the Transgender Population in Baixada Santista of the state of São Paulo, conducted through a structured questionnaire administered between August and December 2023. The outcomes were nutritional status and food and nutrition insecurity (FNI). The association analysis was performed using Fisher's exact test. Results A total of 237 people took part in the study. High prevalence of FNI was associated with an income of less than 2 minimum wages (p < 0.001), difficulty finding a job (p < 0.001) and lack of family support related to gender (p = 0.001). Difficulty reading/writing (p = 0.025) and proximity to an open-air market (p = 0.033) were negatively or positively associated with adequate nutritional status, respectively. Conclusion The high prevalence of FNI among the most vulnerable population and the adequate nutritional status associated with proximity to open-air markets indicate the need for policies aimed at reducing inequities and expand access to adequate food.